Analysis of the Strategy of the General Election Commission (KPU) of Serang Regency in Implementing Voter Education Socialization in the 2024 Election - Maesaroh, Mamay; Fitrayadi, Dinar Sugiana (CV. Rayyan Dwi Bharata, 2024)
This research aims to find out: (1) the strategy of the Serang Regency KPU in implementing voter education outreach, (2) the challenges faced by the Serang Regency KPU in implementing voter education outreach, (3) the Serang Regency KPU's efforts in implementing voter education socialization. This research was conducted using descriptive qualitative methods. Data collection was carried out using observation interviews and documentation and data validity using triangulation. The results of this research show that the strategy used by the Serang Regency KPU is an Offensive strategy, namely a strategy to expand the market and penetrate the market, as well as a defensive strategy, namely defending the market. The challenge in implementing voter education outreach is people's behavior towards elections. Then the efforts made by the Serang Regency KPU in implementing voter education outreach, namely direct and indirect outreach. As for conducting voter education outreach, the Serang Regency KPU has done it according to budget and optimally.